Model Pembelajaran Moral dan Etika Kedokteran pada Mahasiswa, di F.K. Widya Mandala Surabaya - Kusuma Tirtahusada; Willy F. Maramis (JURNAL WIDYA MEDIKA, 2018)
The increasing conciousness on law and personal right among people, must be responded by medical doctors with increasing their attention on medical ethics when providing medical practice, to avoid malpractice. Ethics and medical law are closely related. Attention and learning medical ethics must begin early during medical study, and continue as long as the study. Widya Mandala medical faculty provide a programe called “Ethical Dilemma Discussion”. Begins from the first semester, designed for seven semesters. The programme consists of small group weekly discussions on moral dilemma cases, ten times for each semester, plus classes on morals, philosofy of man, bioethics, social ethics, behavioral sciences in medicine and medical law. Every student must be involved in each dilemma case discussion, express his/her opinion and the reasoning. The discussion attend to the six stages of L. Kohlberg’s moral development. Each dilemma case being analized according to the six principals of Beauchamp and Childress, those are personal autonomy, veracity, beneficence, nonmaleficence, confidentiality, justice. According to reports from students in internship, they feel at easy when discussing dilemma cases in hospital, because they are familiar with moral dilemma dialogues already